Pengaruh Kualitas Produk dan Komunikasi Marketing pada Brand Image serta Dampaknya terhadap Loyalitas Pelanggan pada Produk Sarung di Surabaya - Pontjo Bambang; yesa ramadhani (Jurnal Manajemen dan Keuangan, 2021)
The purpose of this study was to empirically examine the effect of product quality on consumer brand image, the effect of marketing communication on consumer brand image, and the effect of brand image on loyalty. This study uses primary and secondary data sources obtained directly by distributing 100 questionnaires to respondents. The sampling method is non-probability with a pirposive sampling technique. The criteria for respondents are male, the research method uses SEM (Structural Equation Modeling) analysis. The findings of this study are, The first hypothesis which states that product quality affects brand image and is proven significantly, the second hypothesis which states that marketing communication affects brand image is not proven significantly, the third hypothesis which states that brand image affects customer loyalty is proven significantly